Family Tasks in 3M Plus Behavior with Dengue Hemorrhagic Fever (DHF) Prevention - Evi Lusita; Robert Anderson (PT. Griya Eka Sejahtera, 2022)
Background: The spread of dengue hemorrhagic fever can be caused by many factors, one of which is the lack of family duties in preventing. This study aimed to know the role of the family in preventing dengue hemorrhagic fever in the community. Methods: The research design used was observational using cross sectional method and using a questionnaire sheet instrument. The population in this study were 45 respondents. The sample size is 45 respondents using total sampling technique, while to determine the relationship between variables used Spearman rank test with a significant level of 0.05.Results: The results showed that almost all (33%) had not performed the 3M Plus Behavior. The results of the Spearman rank statistical test simultaneously have a family task relationship in 3M Plus behavior with a significant value = 0.000 < 0.05, then reject H0. While the individual test only family tasks that affect the behavior of 3M Plus with p value = 0.035 < 0.05.Conclusion: Family tasks affect the behavior of 3M Plus with dengue hemorrhagic fever prevention because the family has done five forms of family tasks. In the future, the family will be able to carry out 3M plus behavior and try to deal with it appropriately through five forms of family tasks